2009
DOI: 10.1055/s-0029-1243315
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Patent Ductus Arteriosus: Indomethacin or Ibuprofen?

Abstract: We compared ibuprofen and indomethacin for the treatment of patent ductus arteriosus (PDA) in preterm infants. A retrospective comparative study was conducted at a pediatric tertiary center in preterm infants diagnosed with PDA. Infants born from January 2000 to June 2003 were treated with indomethacin, whereas infants born from July 2003 to November 2005 were treated with ibuprofen. The two treatment groups were compared. Demographic data and clinical, laboratory, and outcome data were collected from the medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 47 publications
0
24
2
Order By: Relevance
“…Both intravenous indomethacin (RR 2.39, 95% CI 2.05 to 2.78) and intravenous ibuprofen (RR 2.40, 95% CI 2.03 to 2.84) closed a PDA more effectively than placebo. Other studies [98, 99] have shown a similar efficacy of the two drugs. The two drugs also have a similar failure rate for PDA closure, ranging between 0-50%; Ohlsson et al [100] performed a meta-analysis on data from 19 trials (n=956 infants) for failure rates after 1-3 doses of ibuprofen compared to indomethacin.…”
Section: Management Of Neonatal Pdamentioning
confidence: 59%
“…Both intravenous indomethacin (RR 2.39, 95% CI 2.05 to 2.78) and intravenous ibuprofen (RR 2.40, 95% CI 2.03 to 2.84) closed a PDA more effectively than placebo. Other studies [98, 99] have shown a similar efficacy of the two drugs. The two drugs also have a similar failure rate for PDA closure, ranging between 0-50%; Ohlsson et al [100] performed a meta-analysis on data from 19 trials (n=956 infants) for failure rates after 1-3 doses of ibuprofen compared to indomethacin.…”
Section: Management Of Neonatal Pdamentioning
confidence: 59%
“…Before treatment, creatinine serum concentrations were 0.93±0.20 mg/dL (ibuprofen) and 0.96±0.21 mg/dL (indomethacin) (were not significantly different); after treatment, the serum creatinine concentrations were 0.98±0.24 mg/dL (ibuprofen; P <0.005) and 1.06±0.24 mg/dL (indomethacin; P <0.005) 15. The ibuprofen serum concentration was 1.05±0.36 mg/dL and the serum indomethacin concentration was 1.33±0.46 mg/dL ( P <0.001) 24 hours after administration 22. During the period 2–7 days after treatment, the ibuprofen serum creatinine concentration was 1.11±0.39 mg/dL and the indomethacin serum creatinine concentration was 1.53±0.5 mg/dL ( P <0.001) 22.…”
Section: Resultsmentioning
confidence: 86%
“…The pharmacological basis for the medical treatment of PDA was found, and consists of the inhibition of prostaglandin E 2 by cyclooxygenase inhibitors 822. Indomethacin was the first cyclooxygenase inhibitor to enter clinical use for the therapeutic treatment of PDA; it has been used for many years, and is still used today.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment with ibuprofen is safer, decreasing the risk of renal failure, and hyponatremia. 26 There are conflicting results about the ductal closure rate by oral indomethacin and oral ibuprofen. Fakhrae et al 27 found that the patent ductus arteriosus is closed in all preterm infants (100%) treated with oral ibuprofen and Ibuprofen and indomethacin in neonates Pacifici GM recém-nascidos maduros, o canal arterial se fecha após o nascimento.…”
Section: ■ Discussionmentioning
confidence: 99%